The modeling of quasi-periodic oscillations propagation in the solar corona - N. K. Shividov; A. K. Baltykov; T. V. Velegurin; G. A. Mankaeva; B. B. Mikhalyaev (Современная наука и инновации)
In the general problem of oscillations observed in the solar corona, a particularly intriguing position is occupied by quasi-periodic oscillations, which are often observed in coronal holes. Most often, periods are observed in pairs of close values. Among the possible explanations of this phenomenon, we consider the dispersion of acoustic waves under the influence of thermal conductivity. The possibility of the appearance of pairs of periods may be due to the existence of a minimum at the group velocity, which is realized under the conditions available in the corona. We show how this works, and also claim that this mechanism can serve for the purposes of coronal seismology to determine the parameters of coronal plasma.